In-situ diffuse reflective infrared Fourier transform spectroscopy (DRIFTS) study on Ni passivation in FCC catalysts from boron-based technology - Claire Chunjuan Zhang; Jian Shi; Sage Hartlaub; Joseph P. Palamara; Ivan Petrovic; Bilge Yilmaz (Catalysis Communications, 2021)
Fluid Catalytic Cracking (FCC) is a crucial refining process supplying majority of gasoline used worldwide as well as other key building blocks for chemical industry. Nickel, a contaminant in crude oil, deposits on FCC catalysts and induces unwanted dehydrogenation reactions, inhibiting the FCC unit from reaching optimal operation. We describe a new spectroscopic methodology to characterize the impact of boron interaction on nickel in FCC catalysts through a trend analysis of CO DRIFTS for FCC catalysts from boron-based technology. Results obtained by the new method provide direct spectroscopic evidence of boron effect on nickel passivation by decreasing reducibility of nickel.